Komunikasi Matematis Tulis Siswa SMP pada Materi Aljabar Ditinjau dari Kemampuan Matematika - Santoso, Wahyu; Purwanto, Purwanto; Subanji, Subanji (Mathematics Education Study Program, 2023)
This study aims to describe the written mathematical communication of class IX-F students of SMPN 2 Sumberpucung in solving algebraic problems in terms of mathematical ability. This study uses a qualitative method with a descriptive research type. There were 6 subjects in this study who were selected based on the test scores at the end of the odd semester in mathematics and taking into account the teacher's suggestions representing each category of high, medium, and low mathematical ability. Based on the research, it was found that the students with high mathematical abilities could understand the problems given, could state the information provided and the questions asked, could make a settlement plan, could solve the problems given according to the completion steps used with the correct results, could write conclusions of the solutions obtained. Students with mathematical abilities currently know the information contained in the problem but are unable to understand the given problem, can mention the information provided and the questions asked, can make a settlement plan, can solve the problem according to the completion steps used with poor results correctly, can write conclusions from the solutions obtained. Students with low mathematical abilities cannot understand the problem given, can mention the information provided and the questions asked, cannot make a settlement plan, cannot solve the problem given according to the completion steps used with incorrect results, and cannot write down conclusions from the solutions obtained.